The Impact of Macro News and Central Bank Communication on Emerging European Forex Markets - Balazs Egert; Even Kocenda (Center for Economic Studies and ifo Institute (CESifo), 2013)
We employ two-stage empirical strategy to analyze the impact of macroeconomic news and central bank communication on the exchange rates of three Central and Eastern European (CEE) currencies against the euro. First we estimate the nominal equilibrium exchange rate based on a monetary model. Second, we employ a high-frequency GARCH model to estimate the effects of the news and communication along with the estimated exchange rate misalignment on exchange rate as well as its volatility. Analysis is performed during the pre-crisis (20042007) and crisis (20082009) periods. CEE currencies react to macroeconomic news during both periods in an intuitive manner that corresponds to exchange rate-related theories. Responsiveness of the currencies to central bank verbal interventions becomes important only during the crisis period, though.
Keywords: E31; F31; O11; P17; 330; exchange rate; macroeconomic news; central bank communication; monetary model; Central Europe; European Union